Biased immunoglobulin light chain use in the Chlamydophila psittaci negative ocular adnexal marginal zone lymphomas. Issue 5 (28th March 2013) - Zhu, Daxing; Lossos, Chen; Chapman‐Fredricks, Jennifer R.; Lossos, Izidore S.
<x xml:space="preserve">Abstract</x> Ocular adnexal mucosa associated lymphoid tissue lymphomas (OAMALTL) are the most common lymphomas of the eye. The potential roles for specific antigens in these lymphomas are still controversial. Previously we examined IGHV usage and mutations in Chlamydophila (C) psittaci‐negative OAMALTL, demonstrating biased use of the IGHV4 family and IGHV4–34 gene and evidence for antigen selection. Herein, we examined the IGKV/IGLV gene usage and mutations in 34 C. psittaci‐negative OAMALTL originating from the orbit (15), conjunctivae (14), and lacrimal gland (5). Clonal potentially functional IGKV/IGLV gene sequences were identified in 30 tumors (18 kappa and 12 lambda). An overrepresentation of the IGKV4 family (P < 0.01) was observed. The IGKV3–20*01 allele was used at a greater frequency than in normal peripheral blood B‐lymphocytes (P = 0.02) and commonly paired with the IGHV4–34 allele. Twenty‐seven of the 30 unique light chain sequences displayed mutations from germline and evidence for antigen selection. Overall our findings demonstrate that in C. psittaci‐negative OAMALTL there is a biased usage of IGKV families and genes, which harbor somatic mutations. These findings and the specific paring between the IGKV3–20*01 and IGHV4–34 alleles suggest that specific antigens could play an important role in the pathogenesis of these lymphomas. Am. J. Hematol. 88:379–384, 2013. © 2013 Wiley Periodicals, Inc.